Home environment and early development of rural children: Evidence from Guizhou province in China - Lena Kuhn; Chengfang Liu; Tianyi Wang; Renfu Luo (International Journal of Environmental Research and Public Health, 2021)
Delays in early child development are among the aspects underlying the persistent developmental gaps between regions and social strata. This study seeks to examine the relationship between the home environment and early child development in less-developed rural areas by drawing on data from 445 children from villages in Guizhou province in southwest China. A demographic questionnaire, the Home Observation Measurement of the Environment (HOME), and the Bayley Scales of Infant Development, version III (BSID-III), were used to measure the child's demographic characteristics, home environment, and early development outcomes, respectively. Our data show that the sample children suffer a delay in various dimensions of child development and a deficit in the HOME scale. The results from a hierarchical regression model suggest that the availability of learning material at home, caregivers' responsiveness and organization sub-scales are significantly positively correlated with the early development of sample children, after controlling for general socioeconomic status, health, and nutrition, and this correlation differs by gender. These results imply that the provision of learning material to households, promoting caregivers' responsiveness and organization in less-developed rural areas could improve early child development among deprived children.
Keywords: 330; home environment; learning material; early child development; gender gap; rural China